Contrast‐Enhanced Ultrasound in Small Intestinal Ischemia: Proof of Concept. (8th June 2021) - Gummadi, Sriharsha; Koenig, George; Wessner, Corinne E.; Machado, Priscilla; Stem, Jonathan; Forsberg, Flemming; Liu, Ji‐Bin; Lyshchik, Andrej; O'Kane, Patrick; Eisenbrey, John R.
Abstract : Background: Small intestinal ischemia is a challenging diagnosis to make, even with the combination of imaging, laboratory analysis, and physical exam. This pilot study investigated the role of CEUS in evaluating small bowel wall vascularity in participants with suspected ischemia. Methods: In this IRB‐approved pilot study, CEUS using perflutren lipid microspheres (DEFINITY®; Lantheus Medical Imaging Inc., N. Billerica, MA) was performed on participants determined by the clinical surgical team to have concerns for small intestinal ischemia. CEUS interpretations were performed at both the bedside and later by a blinded radiologist and compared to clinical imaging, surgical findings, or long‐term clinical outcomes. Results: Fifteen CEUS examinations were performed on 14 participants. Five of the participants underwent exploratory laparotomy. Of these, one had small intestinal ischemia (without necrosis). Point of care CEUS demonstrated no evidence of bowel necrosis in any case, and delayed enhancement (indicative of intestinal ischemia) in three cases, resulting in a sensitivity of 100% (95% CI 2.5–100%) and specificity of 85.7% (95% CI 57.2–98.2%). CEUS correctly ruled out ischemia in 91.7% of cases with CT suspicion of small bowel obstruction and 60% of cases that underwent surgical intervention. Additionally, the rate of agreement between bedside interpretation and later radiologist read was high (93%). Conclusions: CEUS is uniquely positioned for evaluating the small intestine, because of its high temporal resolution and immediacy of results. Combined with multi‐sectional imaging for focal areas of ischemia and/or clinical suspicion for pan ischemia, CEUS may be a useful rule out test for small intestinal ischemia.